Smart Electricity Billing System Using Blockchain Technology - Aiman, Shafiq; Hassan, Suhaidi; Habbal, Adib; Rosli, Athirah; Mohd Shabli, Ahmad Hanis (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Nowadays, many home appliances use electricity to operate. However, prediction of the electricity usage is not easy and accurate. A prepayment scheme provides the better way to forecast domestic electricity usage. Traditionally, the prepayment scheme is based on the centralized server or the standalone embedded machine, but the centralized service is highly vulnerable to security threats and potential attacks. The purpose of this paper is to describe our design of a peer-to-peer token bill system for the domestic electricity distribution. It also describes the trusted information transaction among the Internet-of-Things devices. In addition, we provide a conceptual overview of the blockchain-based Wattcoin payment system. In this system, a wallet is created by using the cryptography technique that generates private key, public key and the wallet address. Then, the transaction is done when the digital signature is used to authenticate every transaction floating in the network. Moreover, this paper illustrates blockchain message protocol for message exchange among devices.